Evolutionary Biology of Aging. - Rose, Michael R. (Oxford University Press, 1994)
The author of this monograph proposes an evolutionary theory of senescence - that the force of natural selection declines proportionally with age after the onset of reproduction. He elaborates with evidence from cell biology, physiology and gerontology.